2014
DOI: 10.1039/c3cc48804g
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, structure and reactivity of FeII/III–NH3 complexes bearing a tripodal sulfonamido ligand

Abstract: Complexes [MnMST(NH3)]n-3 (Mn = FeII, FeIII, GaIII) were prepared and each contains a intramolecular hydrogen bonding network involving the ammonia ligand. Deprotonation of the FeIII–NH3 complex afforded a putative [FeIIIMST(NH2)]− species whose reactivity has been explored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…Our group has specialized in the development of ligand platforms that promote intramolecular H-bonding networks to investigate their influence on the secondary coordination sphere. One design uses the symmetrical urea ligand [H 3 buea] 3– (Figure A) that provides a cavity with three H-bond donors positioned to stabilize monomeric Mn, Fe, Co, and Ni complexes with terminal oxido/hydroxido ligands. , We found that the strongly anionic ligand field provided by the monodeprotonated urea groups also assists in stabilizing high-valent species that includes Mn V –oxido and Mn IV –hydroxido complexes. We have also examined the chemistry of tripodal ligands such as [RST] 3– (Figure B) which contains deprotonated sulfonamide units that also function as H-bond acceptors. Recently, hybrid tripods were introduced that contain both urea and sulfonamido groups to vary the intramolecular H-bonding network that surrounds Co–OH units (Figure C) . These studies showed that deprotonated sulfonamido ligands are useful H-bond acceptors; however, they do not provide a sufficient primary coordination sphere to stabilize monomeric M–OH complexes with oxidation states greater than 3+.…”
Section: Introductionsupporting
confidence: 64%
See 1 more Smart Citation
“…Our group has specialized in the development of ligand platforms that promote intramolecular H-bonding networks to investigate their influence on the secondary coordination sphere. One design uses the symmetrical urea ligand [H 3 buea] 3– (Figure A) that provides a cavity with three H-bond donors positioned to stabilize monomeric Mn, Fe, Co, and Ni complexes with terminal oxido/hydroxido ligands. , We found that the strongly anionic ligand field provided by the monodeprotonated urea groups also assists in stabilizing high-valent species that includes Mn V –oxido and Mn IV –hydroxido complexes. We have also examined the chemistry of tripodal ligands such as [RST] 3– (Figure B) which contains deprotonated sulfonamide units that also function as H-bond acceptors. Recently, hybrid tripods were introduced that contain both urea and sulfonamido groups to vary the intramolecular H-bonding network that surrounds Co–OH units (Figure C) . These studies showed that deprotonated sulfonamido ligands are useful H-bond acceptors; however, they do not provide a sufficient primary coordination sphere to stabilize monomeric M–OH complexes with oxidation states greater than 3+.…”
Section: Introductionsupporting
confidence: 64%
“…2830 We have also examined the chemistry of tripodal ligands such as [RST] 3– (Figure 1B) which contains deprotonated sulfonamide units that also function as H-bond acceptors. 3134 Recently, hybrid tripods were introduced that contain both urea and sulfonamido groups to vary the intramolecular H-bonding network that surrounds Co–OH units (Figure 1C). 18 These studies showed that deprotonated sulfonamido ligands are useful H-bond acceptors; however, they do not provide a sufficient primary coordination sphere to stabilize monomeric M–OH complexes with oxidation states greater than 3+.…”
Section: Introductionmentioning
confidence: 99%
“…The [Fe IV poat­(O)] − complex was produced from [K­(18c6) 2 ]­[Fe II poat], whose properties are consistent with a four-coordinate Fe II complex having an S = 2 spin ground state (Scheme , see experimental section). , We found that 18-crown-6 (18c6) increases the solubility of this Fe II complex and sequesters the K + counterion to prevent its interaction with the PO moieties of the [poat] 3– ligand. [K­(18c6) 2 ]­[Fe II poat] was treated with isopropyl 2-iodoxybenzoate (IBX-iPr) in a DMF/THF mixture at −60 °C (Scheme ), and spectrophotometric monitoring of this reaction showed the growth of several new absorption bands (Figure ).…”
Section: Results and Discussionmentioning
confidence: 99%
“…The shorter Fe-N10 bond of 2.010(2) in 3 Tol -NH 3 + vs 2.072(2) for 1 Tol -NH 3 confirmed the oxidation of the Fe center from +II to +III and is a rare example of a Fe-NH 3 adduct in the +III oxidation state. 64,65 The compound demonstrates the ability of the B 2 Pz 4 Py platform to stabilize and access higher oxidation state complexes.…”
Section: Chemical Science Accepted Manuscriptmentioning
confidence: 97%